Songs of ourselves writings by Filipino women in English - Manlapaz, Edna Zapanta (Pasig Anvil Publishing, Inc., 1994)
From time to time during the near hundred years of Philippine Literature in English, ... consciousness-of-self-as-Filipino-woman has expressed itself through the voices of writers. But their speech has not always been listened to with the attentiveness conventionally claimed by male discourse. The silent assumption appears to be that women's stories, because often confined within the space of closed rooms and fenced yards, have nothing significant to say about the world outside. Private space cannot accommodate public issues; fairy tales and lullabies and cuentos cannot articulate political statements; small talk cannot en-compass big questions. this anthology does more than affirm these experiences of women as valid and valuable in themselves, its privileges them.
Why So Pale and Wan Fond Lover? -- They Flee From Me That Sometime Did Me Seek -- The Authors Epitaph Made By Himself -- A Song -- The Procession of The Seasons -- The Fly -- The Grasshopper -- Love Armed -- Those Winter Sundays -- The Three Fates -- Amends -- Lament -- So Well Go No More A Loving -- Pied Beauty -- A Birthday -- Ozymandias -- As Loving Hind That Hartless Wants Her Deer -- From On My Dreaming of my Wife -- The Rights of Woman -- The Hunting of The Hare -- The Chimney Sweepers Complaint -- On His Blindness -- Elegy Written in a Country Churchyard -- From An Essay on Man -- Childhood -- Praise Song For My Mother -- The Trees -- You Cannot Do This ? Friend -- Times Fool -- Meeting At Night.
Keywords: Philippine literature (English).; Philippine literature (English) -- Women authors; Short stories, Philippine (English) -- Women authors; Philippine poetry (English) -- Women authors